2002
DOI: 10.1104/pp.004432
|View full text |Cite
|
Sign up to set email alerts
|

A Strobilurin Fungicide Enhances the Resistance of Tobacco against Tobacco Mosaic Virus and Pseudomonas syringae pvtabaci  

Abstract: The strobilurin class of fungicides comprises a variety of synthetic plant-protecting compounds with broad-spectrum antifungal activity. In the present study, we demonstrate that a strobilurin fungicide, F 500 (Pyraclostrobin), enhances the resistance of tobacco (Nicotiana tabacum cv Xanthi nc) against infection by either tobacco mosaic virus (TMV) or the wildfire pathogenPseudomonas syringae pv tabaci. F 500 was also active at enhancing TMV resistance in NahGtransgenic tobacco plants unable to accumulate sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
10

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 32 publications
0
79
0
10
Order By: Relevance
“…Some researches have evaluated the action of ASM and pyraclostrobin in the defense of plants against bacteria. Herms et al (2002) demonstrated that pyraclostrobin increased tobacco resistance to Tobacco mosaic virus and Pseudomonas syringae pv. tabaci.…”
Section: Resultsmentioning
confidence: 99%
“…Some researches have evaluated the action of ASM and pyraclostrobin in the defense of plants against bacteria. Herms et al (2002) demonstrated that pyraclostrobin increased tobacco resistance to Tobacco mosaic virus and Pseudomonas syringae pv. tabaci.…”
Section: Resultsmentioning
confidence: 99%
“…tabaci. Pyraclostrobin also increases TMV resistance in NahG-transgenic tobacco plants (Herms et al 2002), suggesting that this fungicide enhances TMV resistance in tobacco either by acting downstream of SA in the SA signaling cascade or by functioning independently of SA. Pyraclostrobin did not cause the accumulation of SA-inducible PR-1 defense proteins in infiltrated leaves.…”
Section: Priming By Chemicals For Potentiated Responses To Biotic Strmentioning
confidence: 99%
“…[15]. In a recent report it was evident that not only fungal diseases, viral disease like TMV infection is also restricted in Tobacco plant pre-treated with pyraclostrobin [16]. Though several fungicides like carbendazim, validamycin and several triazoles like propiconazole, hexaconazole have been recommended for sheath blight disease management but in areas which regularly suffer with severe sheath blight disease, application of any strobilurin fungicides viz.…”
Section: Resultsmentioning
confidence: 99%